2010
DOI: 10.1213/ane.0b013e3181c88fcd
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management of Patients with Huntington Disease

Abstract: Contrary to previous case reports, we found that patients with HD have normal responses to general anesthesia. However, the anesthesiologist should be aware of interactions between anesthetics and psychiatric medications frequently used by these patients. Measures should also be taken to minimize the risk of pulmonary aspiration because bulbar dysfunction may be a manifestation of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Patients receive psychotropic medications (antipsychotics, antidepressants, benzodiazepines and antiepileptics) which can interact with anaesthetic agents. [2] They may not be compliant with the treatment as also the case with our patient.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Patients receive psychotropic medications (antipsychotics, antidepressants, benzodiazepines and antiepileptics) which can interact with anaesthetic agents. [2] They may not be compliant with the treatment as also the case with our patient.…”
mentioning
confidence: 69%
“…[5] Contrary to above, in a large review of 11 patients, authors have reported normal response to thiopentone and propofol and did not observe prolonged amnesia with midazolam or abnormal response to succinylcholine. [2] Safe use of total intravenous anaesthesia with remifentanil and propofol is reported. [6] Rocuronium use and reversal of neuromuscular blockade with sugammadex is reported, considering aggravation of choreiform movements with neostigmine and anticholinergics.…”
mentioning
confidence: 99%
“…HD is characterised by involuntary choreatic movements, associated with respiratory compromise, oropharyngeal dysphagia, orobuccolingual dyskinesia and a loss of facial, truncal and limb motor control 5. Despite preoperative fasting, the abnormal oesophageal and gastric motility due to bulbar dysfunction and the presence of a small feeding NGT may not guarantee that the stomach will be completely empty following NGT suction 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were case reports and case series about anesthetic management of Huntington Chorea patients, there is only one case report was detected in the literature about the administiration of sugammadex in those patients [3][4][5][6][7]. Sugammadex is a gamma-cyclo dextrin structured agent that was used to reverse steroidal neuromuscular blocker agents such as rocuronium and vecuronium.…”
Section: Discussionmentioning
confidence: 99%